EDUCATING TECHNICAL STUDENTS IN READING AND TRANSLATION SKILLS TEXTS IN THE ENGLISH LANGUAGE - Zukhra Allaberdievna Zulfiqorova (Bright Mind Publishing, 2025)
The ability to read and translate materials in English is becoming increasingly important for technical workers. The fact that domestic businesses employ a lot of foreign equipment that needs to be handled, maintained, and repaired by professionals is a prerequisite for this requirement. Furthermore, it is common for Russian and Uzbek experts to go abroad for training in order to advance their professional credentials, which calls for fluency in English. The author of this page makes an effort to organize the most promising tools for training technical specialty students to read and translate English-language materials.
Keywords: English language, teaching technologies, reading and translating texts, technical specialties, instructing students, colloquial language, knowledge, skills.